1998
DOI: 10.1292/jvms.60.1265
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the Blood Endotoxin Concentration and Prognosis in Dogs with Pyometra.

Abstract: ABSTRACT. The blood concentrations of endotoxin in dogs with pyometra (n=45) were compared with those in healthy dogs (n=17). The blood endotoxin concentrations in the healthy dogs (n=17), in those with good prognosis (n=41) and those with poor prognosis (n=4) were 3.4 ± 2.8 pg/ml, 9.5 ± 11.3 pg/ml and 74.2 ± 18.3 pg/ml, respectively. The concentrations in the dogs with good prognosis and poor prognosis were significantly (p<0.01) higher than those in the healthy dogs. The dogs with poor prognosis had signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 11 publications
2
37
1
5
Order By: Relevance
“…Specific kinds of bacteria were not detected by the bacteria test, with common bacteria such as staphyrocuss and E. coli which usually exist in the intestine being discovered. Okano et al [10] reported that the endotoxin of bacteria in serum was elevated in dogs with pyometra. Although the results from the serum test for endotoxin were negative, endotoxin might play an important role in enhancing the severity of the condition in dogs, judging from the highly increased leukocyte count and the ineffectiveness of any kind of antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Specific kinds of bacteria were not detected by the bacteria test, with common bacteria such as staphyrocuss and E. coli which usually exist in the intestine being discovered. Okano et al [10] reported that the endotoxin of bacteria in serum was elevated in dogs with pyometra. Although the results from the serum test for endotoxin were negative, endotoxin might play an important role in enhancing the severity of the condition in dogs, judging from the highly increased leukocyte count and the ineffectiveness of any kind of antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Common bacteria isolated from pyometra infections in bitches are gram negative bacteria such as Escherichia coli, Klebsiella spp., Pasteurella, Proteus, Pseudomonas spp., which releases lipopolysaccharide structured endotoxine from their cell wall 1, [5][6][7][8] . In the case that infection with predominantly gram-negative bacteria such as Escherichia coli are isolated, endotoxemia has been demonstrated in bitches with pyometra 6,9 . According to the main theories, this bacteria rise as ascending bacterial infections from the host's vaginal/intestinal flora or as descending from urinary tract infection 8, [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Also the suppression of bone marrow activity by toxemia is caused anemia and in cases of pyometra are remarkably increase leucocyte 3,7,13, 14 . In recent years, blood endotoxin levels have been reported in bovine gangrenous mammilitis and equine colic, but little attention has been paid to blood endotoxin levels in small animals 6 . In case of pyometra, to measure the concentration of endotoxin in blood is considerable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A HEC-Piometra é uma afecção de incidência elevada, diagnosticada em 25% das cadelas com idade entre 6 e 10 anos (EGENVALL et al, 2001 Estudos demonstram que a endotoxemia é responsável pelas alterações sistêmicas em cadelas com endometrite-piometra e as concentrações plasmáticas da endotoxina estão diretamente relacionadas à evolução desfavorável da doença (WESSELS;WELLS, 1989;OKANO et al, 1998;FRANSSON et al, 1997 Endometrite-Piometra possa ser justificada pela ação da PGE2 na vasodilatação e supressão da resposta imune, com consequente piora do quadro clínico. Ademais, a correlação negativa entre o número de leucócitos totais e os índices hemodinâmicos caracteriza a resposta do organismo frente à ação das endotoxinas, bem como a ação das prostaglandinas na modulação da resposta inflamatória uterina.…”
Section: Avaliação Clínica E Laboratorialunclassified